New experimentalism in design research: Characteristics and interferences of experiments in science, the arts, and in design research - Steffen, Dagmar (Artifact, 2014)
Commonly the term “experiment” is in the first place associated with science, systematic methods and strict principles for the sake of knowledge creation. Nonetheless, the term is widely used across the boundaries of science. The arts attribute artworks likewise as experimental – a usage that is often claimed to be metaphorical, since experiments in the arts (including design) lack the essential attributes that define a scientific experiment.